Individual Choice of a Pension Fund in Russia: Are the Investment Results of the Fund Important? - Tumanyants, Karen; Gulyaeva, Eugenia V. (International Journal of Economics and Financial Issues, 2016)
The paper presents the econometric assessment of the influence on the market positions of the fund of nominal yield volume and the Sharpe ratio formed in the pension savings investment by non-state pension funds in the Russian Federation. Using pair and multiple regression models and also a fixed effects model, the authors did not find any statistically important correlation between the investment results and insured persons’ choice of a pension fund. The results of the study point to weak stimuli for the participants of the pension sphere to improve the investment process quality and deformation of competition in the pension services market. Keywords: yield, Sharpe ratio, competition. JEL Classifications: D40, D12, G23